Facile synthesis of superparamagnetic iron oxide nanoparticles with tunable size: from individual nanoparticles to nanoclusters. (1st October 2017) - Mi, Xuan; Tong, Meikui; Cai, Jia; Su, Hui; Liu, Shiyuan; Ma, Yongjie; Wei, Xunbin; Zhang, Chunfu
Abstract : Superparamagnetic iron oxide nanoparticles (SPIONs) have a wide variety of biomedical applications. Synthesis of SPIONs with well‐defined, tunable size in a facile way is highly desirable. In this work, a one‐pot polyol method was developed for preparation of SPIONs with tunable size and high quality in the presence of poly (acrylic acid) (PAA). By adjusting the amount of PAA used, the isolated nanoparticles and nanoparticle clusters were able to be synthesised. As‐synthesised nanoparticles and nanoclusters were highly stable in physiological conditions. The size of the nanoparticles was 7 ± 1 nm and that for the nanoclusters was 20 ± 2 and 32 ± 3 nm, respectively. The nanoparticles demonstrated good magnetic resonance imaging T 1 and T 2 dual contrast effects ( r 1 = 12.2 mM −1 s −1 and r 2 = 47.5 mM −1 s −1 ), while the nanoclusters exhibited a superior T 2 contrast effect with the transverse relaxivities of 198 mM −1 s −1 (20 ± 2 nm) and 410 mM −1 s −1 (32 ± 3 nm), respectively. More importantly, both the nanoparticles and nanoclusters were highly tolerable by cells.